Edukasi Kesiapsiagaan Kesehatan Reproduksi Keluarga sebagai Upaya Mitigasi Krisis Kesehatan bagi Pasangan Usia Subur - Riska Nuryana; Zuhriana K. Yusuf; Jesica Mulyadi; Sulaiman Putra Nagaring; Sitty Fadhilla Fitrianty Lahay (Jurnal Pengabdian Bidang Kesehatan, 2026)
Reproductive health is a key component of family resilience, particularly for couples of reproductive age (CRA) who face increased risks of unintended pregnancy and limited access to health services during emergencies. Community-based education offers an effective strategy to strengthen reproductive health knowledge and preparedness. This community service program applied a one-group pretest–posttest design using a participatory educational approach. A total of 26 couples of reproductive age from Telaga Jaya District, Gorontalo Regency, participated in the intervention. Educational sessions covered family planning, safe pregnancy, pregnancy danger signs, and reproductive health crisis preparedness. Participants' knowledge was assessed before and after the intervention using a structured questionnaire, and the data were analyzed descriptively to determine changes in knowledge levels. The findings demonstrated a marked increase in participants' knowledge, with the average score rising from 56.4 ± 8.7 before the intervention to 82.3 ± 6.5 afterward. The greatest improvement occurred in family planning knowledge (54.0%), followed by pregnancy danger signs (47.7%), health crisis preparedness (43.2%), and safe pregnancy (42.5%). Moreover, the proportion of participants with high knowledge increased from a minority before the intervention to 70% after completion, while the percentage with low knowledge declined substantially. These results suggest that participatory education effectively enhances reproductive health literacy, promotes active learning, and strengthens family preparedness to address reproductive health challenges in underserved communities.